A new, apparently lotic species of Relictorygmus from the Northern Cape Kamiesberg, South Africa (Coleoptera, Hydrophilidae, Cylominae) - Bilton, David T.; Mlambo, Musa C. (Zootaxa, 2024)
Relictorygmus Seidel, Minoshima, Arriaga-Varela & Fikáček, 2018, the only known African genus of the hydrophilid subfamily Cylominae, currently includes two lentic species from the far southwestern Cape of South Africa. Here Relictorygmus riparius sp. nov. is described, based on specimens collected from wet moss beside a small mountain stream in the Kamiesberg, Northern Cape Province, South Africa, almost 500 km from previously known taxa and the first lotic member of the genus. The new species is compared with the two previously described Relictorygmus, R. trevornoahi Seidel, Minoshima, Arriaga-Varela & Fikáček, 2018 and R. repentinus (Hebauer, 2002) and notes are provided on its ecology at the type locality. This unexpected find suggests that other cylomines may remain undetected in southern Africa, particularly since they can easily be mistaken for species of the morphologically similar, but distantly related, Coelostoma Brullé, 1835.